Revision of the untreated taxa of Melaloncha s. s. bee-killing flies (Diptera: Phoridae) - Brown, Brian V. (Zootaxa, 2006)
The previously untreated sections of the bee-parasitizing, Neotropical phorid genus Melaloncha Brues are revised. A total of 167 species of these strictly New World flies are now recognized, including the following 36 new species: M. acicula, M. berezovskiyi, M. calathea, M. ciliata, M. cordyla, M. crinita, M. declivata, M. dibitettii, M. erinacea, M. feleoae, M. flavilineata, M. forficata, M. gomezi, M. gonzalezae, M. gradata, M. hirsuta, M. immaculata, M. kittsonae, M. lacerna, M. laselvae, M. licina, M. muricata, M. nannocauda, M. oligoseta, M. pilidorsata, M. prostata, M. rasmusseni, M. rodeoensis, M. ruinensis, M. simoni, M. simotris, M. torquata, M. trichopera, M. umbra, M. xanthocauda and M. zurquiensis. Because of insufficient differences among examined specimens, Melaloncha cuspidata Borgmeier is synonymized with M. palpalis Borgmeier (new synonymy). A lectotype is designated for the species M. plaumanni Borgmeier. Hosts and behavior of some species is discussed, and a new key to species and species groups of Melaloncha is presented.